The tribological behaviour of a high nitrogen manganese austenitic stainless steel - Mills, Duncan John (Department of Mechanical Engineering, 2017)
The tribological behaviour of two experimental alloys, namely a high nitrogen manganese austenitic stainless steel and a vanadium micro-alloyed stainless steel is compared to the tribological behaviour of standard stainless steels AISI 304 and AISI 316 and to the wear resistant steel, Hadfields manganese steel. The wear tests performed on these steels were abrasion, abrasion-corrosion and cavitation erosion. The high nitrogen alloy contained 0.63wt% nitrogen and 0.83wt% nickel and was found to have mechanical properties superior to the other steels studied in this thesis. This alloy was also subject to cold deformation and strain ageing and the wear resistance of the material in these different conditions was measured. No mechanical testing was performed on the vanadium micro-alloyed steel because of specimen size constraints. Hardness tests were performed on the high nitrogen alloy after deformation and ageing treatments at different temperatures for different times and the results show an improvement in hardness. Under abrasion Hadfields manganese steel has the best abrasion resistance followed by the vanadium micro-alloyed steel, the high nitrogen alloy and then AISI 316 and AISI 304. The abrasion-corrosion results show that the vanadium micro-alloyed steel and the high nitrogen alloy have the best abrasion-corrosion resistance followed by AISI 316 and AISI 304 and lastly Hadfields manganese steel. The high nitrogen stainless steel shows a decrease in the abrasion resistance with an increase in the amount of prior cold deformation. Strain ageing is found to have no effect on the abrasion resistance. This is in contrast to the results for cavitation erosion where there is an improvement in the cavitation erosion resistance with an increase in the amount of cold deformation. Strain ageing improves the cavitation resistance especially when material with between 16% and 48% prior cold deformation is strain aged Abrasion-corrosion was not performed on the processed material as the test is not sensitive enough to record any differences. For the vanadium micro-alloyed steel it is seen that despite there being an improvement in the hardness of the alloy with increased ageing time there is no corresponding increase in the abrasion resistance. With regard to cavitation erosion resistance, ageing treatments at 700°C lead to an improvement in the steady state erosion rate and an increase in the incubation time. After ageing at 900°C the steady state erosion rate shows no change whilst the incubation time increases.